Enteroendocrine cells are a potential source of serum autotaxin in men - Bolier, Ruth; Tolenaars, Dagmar; Kremer, Andreas; Saris, Job; Pares, Albert; Verheij, Joanne; Bosma, Piter J.; Beuers, Ulrich; Elferink, Ronald P. J. Oude (BBA - Biochimica et Biophysica Acta, 2016)
Serum autotaxin (ATX) activity is significantly increased in cholestatic patients. Our study aimed to unravel the source(s) of ATX in cholestasis.ATX activity and protein were measured in sera of healthy (n=33) and cholestatic patients (n=152), including women with intrahepatic cholestasis of pregnancy. ATX mRNA and protein expression were analyzed in various tissues from mice and men. Induction of ATX activity was assessed in mouse models of extrahepatic (bile duct ligation) and intrahepatic cholestasis (Atp8b1(G308V/G308V), 0.1% cholate-supplemented diet). ATX clearance in cholestatic and control mice was assessed after intravenous injection of recombinant ATX. Human hepatic clearance was estimated by comparing ATX activity in portal and hepatic vein serum.Serum ATX activity and ATX protein concentration tightly correlated under all conditions in patients and controls (p<0.0001). In humans Atx mRNA was highly expressed in small intestine, whereas in mice Atx was expressed mainly in brain and placenta but not in small intestine. Extensive ATX protein expression was identified in human, but not murine intestinal enteroendocrine cells. In murine models of cholestasis and cholestatic pregnancy plasma ATX activity was only mildly elevated (up to 2.1-fold). Atx tissue expression and rATX clearance after parenteral administration did not differ between cholestatic and control mice.Serum ATX activity during cholestasis and itch is enhanced by increased protein concentration rather than enzymatic induction. In mice, clearance of ATX is not affected by cholestasis. Small intestinal ATX expression by enteroendocrine cells might represent an important source of cholestasis-induced serum ATX activity in men.
EVALuna2:2087